1993
DOI: 10.1113/jphysiol.1993.sp019571
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a K(+)‐H+ exchange in trout red blood cells.

Abstract: SUMMARY1. Exposure of trout red blood cells to ,-adrenergic agonist isoprenaline activates a cAMP-dependent Na+-H+ antiport, the movements of protons being compensated by a Cl--OH-(or HCO3) exchange mediated by band 3 protein. The absorption of water osmotically linked to sodium and chloride induces cell swelling.2. In the presence of acetazolamide, anionic exchange is inhibited and activation of cationic exchange resulted in the first 2 min in a strong external acidification and a large internal alkalinizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…A K+-H' exchanger has also been reported to be expressed in the membrane of rabbit corneal epithelium (Bonanno, 1991), carotid body glomus cells (Wilding et al, 1992), red blood cells (Fievet et al, 1993) and Amphiuma erythrocytes (Cala, 1980). In summary, our results demonstrate that BBMV isolated from chicken jejunum express at least two separate cation H+ exchangers, one mainly for K' and one for Na+.…”
Section: Discussionsupporting
confidence: 75%
“…A K+-H' exchanger has also been reported to be expressed in the membrane of rabbit corneal epithelium (Bonanno, 1991), carotid body glomus cells (Wilding et al, 1992), red blood cells (Fievet et al, 1993) and Amphiuma erythrocytes (Cala, 1980). In summary, our results demonstrate that BBMV isolated from chicken jejunum express at least two separate cation H+ exchangers, one mainly for K' and one for Na+.…”
Section: Discussionsupporting
confidence: 75%
“…the taurine pathway as well as Cl--dependent or Cl--independent pathways (Borgese et al 1987a; Garcia-Romeu et al 1991; Motais et al 1991). This difficulty can be circumvented by using acetazolamide (Diamox), which effectively C1--DEPENDENT AND C1--INDEPENDENT CO-TRANSPORT 621 inhibits Cl--OH-exchange as demonstrated in the companion paper (Fievet et al 1993); we showed that in the presence of acetazolamide, Cl-entry via the anion exchanger is completely blocked whereas the activation of Na+-H+ exchange induced large changes in external and internal pH even leading to a reversal of the transmembrane pH gradient. Despite the persistence of this large transmembrane pH gradient, inhibition of the anion exchanger by acetazolamide was clearly maintained during the 1 h experiment.…”
Section: Intracellular Recording Criteriamentioning
confidence: 75%
“…Preparation of cells, determination of cellular ion and water contents and intracellular pH measurements were made as described in the companion paper (Fievet, Guizouarn, Pellissier, Garcia-Romeu & Motais, 1993 …”
Section: C1f-dependent and C1--independent Co-transportmentioning
confidence: 99%
See 1 more Smart Citation
“…This does suggest that the source of the increased plasma K + concentrations may have differed from that of the other monovalent ions. We suspect that this may have reflected an increased K + efflux from erythrocytes (Fievet et al, 1993) and/or other cell types (Bianchini et al, 1991) as a volume-regulatory process during stress. Indeed, turbot red cells showed no cell swelling after stress as determined by their stable MCHC.…”
Section: Discussionmentioning
confidence: 98%